Biparametric Magnetic Resonance Imaging‐Derived Nomogram to Detect Clinically Significant Prostate Cancer by Targeted Biopsy for Index Lesion - Kim, Min Je; Park, Sung Yoon (Journal of magnetic resonance imaging, 2022)
Background Currently, it is necessary to investigate how to combine biparametric magnetic resonance imaging (bpMRI) with various clinical parameters for the detection of clinically significant prostate cancer (csPCa). Purpose To develop a multivariate prebiopsy nomogram using clinical and bpMRI parameters for estimating the probability of csPCa. Study type Retrospective, single‐center study. Subjects Two hundred and twenty‐six patients who underwent targeted biopsy (TBx) for the MRI‐suspected index lesion because of clinical suspicions of PCa. Field strength/sequence A 3 T MRI including turbo spin‐echo T2‐weighted and diffusion‐weighted single‐shot echo‐planar imaging sequences. Assessment Prebiopsy clinical and bpMRI parameters were patient age, biopsy history (biopsy‐naïve or repeated biopsy status), prostate‐specific antigen density (PSAD), Prostate Imaging‐Reporting and Data System version 2.1 (PI‐RADSv2.1), and apparent diffusion coefficient ratio (ADCR). ADCR was defined as mean ADC of the index lesion divided by mean ADC of the contralateral prostatic region. A multivariate prebiopsy nomogram for csPCa (i.e. Gleason sum ≥7) was developed. Area under the curve (AUC) of each parameter and prebiopsy nomogram was assessed. Five‐fold cross‐validation was performed for robust estimation of performance of the prebiopsy nomogram. Statistical tests Logistic regression, receiver‐operating curve, and 5‐fold cross‐validation. P‐value < 0.05 was considered statistically significant. Results Proportion of csPCa was 31.9% (72/226). The AUCs of age, biopsy‐naïve status, PSAD, PI‐RADSv2.1, ADCR, and prebiopsy nomogram were 0.657 (95% confidence interval [CI], 0.580–0.733), 0.593 (95% CI, 0.525–0.660), 0.762 (95% CI, 0.697–0.826), 0.824 (95% CI, 0.770–0.878), 0.829 (95% CI, 0.769–0.888), and 0.906 (95% CI, 0.863–0.948), respectively: AUC of nomogram was significantly different than that of individual parameter. In the 5‐fold cross‐validation, the mean AUC of the prebiopsy nomogram for csPCa was 0.888 (95% CI, 0.786–0.983). Data conclusions This multivariate prebiopsy nomogram using clinical and bpMRI parameters may help estimate the probability of csPCa in patients undergoing TBx. ADCR seems to enhance the role of bpMRI in detecting csPCa. Level of evidence 3 Technical Efficacy Stage 2.